APPLICATION OF BLOCK CHAIN TECHNOLOGY IN MANUFACTURING INDUSTRIES TO OPTIMIZE SUPPLY CHAIN AND LOGISTIC OPERATIONS (International Journal of Engineering Sciences & Management Research, 2018)
Now a days supply chain and logistics are two core issues need to be addressed by Indian manufacturing giants as these operational have been suffering from various factors like competition by global traders , outsourcing, ever diversed geographies etc. Simultaneously logistic operations are also facing problems like improper planning, irregular procurement movements, inferior stationing etc. In the most recent Block Chain Technique has emerged as a key solution to address above inconsistencies to achieve transparency, real-time monitoring and proactive view.